How Job Involvement Moderates the Relationship Between Organizational Commitment and Job Satisfaction: Evidence in Vietnam - Chi, Hsinkuang; Yeh, Hueryren; Nguyen, Khanh-Van Ho (Advances in Social Sciences Research Journal, 2018)
The purpose of this study is to investigate whether there are significant relationships among perceived organizational support, organizational commitment, job involvement, job commitment, and job satisfaction. The sample for this study included 275 employees in Vietnam. The findings revealed that organizational commitment had a partial mediating effect between perceived organizational support and job satisfaction. Furthermore, the study found that job involvement had a moderating effect on the relationship between organizational commitment and job satisfaction.